2014
DOI: 10.1007/s12032-014-0237-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of measuring expression levels of Stanniocalcin 2 in patients with colorectal cancer

Abstract: Stanniocalcin 2 (STC2) is a novel member of the Stanniocalcin family, the function of which remains unclear. Its expression is clinically significant in several cancers. The aim of this study was to evaluate the clinical value of measuring expression levels of STC2 in colorectal cancer (CRC) patients. A total of 47 tumor and matched tumor-free margin samples were obtained during surgery. The STC2 mRNA expression level in tumor and marginal tissue was examined by real-time quantitative PCR. STC2 mRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Similarly, Hashemzadeh et al reported the same result for the STC2 gene in CRC. 49 Taken together, our data may support the rare literature that shows field cancerization in CRC. 50 Furthermore, combining multiple gene expression data and correlating the data to distances from tumor margins might be effective for delineating the tumor margin and molecular alterations that are characteristic of field of cancerization in CRC.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, Hashemzadeh et al reported the same result for the STC2 gene in CRC. 49 Taken together, our data may support the rare literature that shows field cancerization in CRC. 50 Furthermore, combining multiple gene expression data and correlating the data to distances from tumor margins might be effective for delineating the tumor margin and molecular alterations that are characteristic of field of cancerization in CRC.…”
Section: Discussionsupporting
confidence: 85%
“…The differential expression levels of STC2 have certain guiding significance for the prediction, metastasis and prognosis of various malignant tumors (24). Studies have shown that STC2 is involved in the development of CRC (25,26). However, its mechanism of action is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the expression level of STC2 in CRC patients is higher than that in normal tissues, and that the expression level of STC2 is related to tumor size and pathological grade (25,27,28). In the present study, it was demonstrated that STC2 was obviously increased in CRC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Stanniocalcins (STCs) are glycoprotein hormones, and several investigators have reported their role in calcium and phosphate homeostasis (Ishibashi and Imai, 2002; Chang et al , 2003). Upregulation of STC2 has been reported in several cancers (Ieta et al , 2009; Kita et al , 2011; Arigami et al , 2013; Fang et al , 2014; Hashemzadeh et al , 2014). High levels of STC2 expression were correlated with worse prognoses of cervical cancer patients after RT (Shen et al , 2014).…”
Section: Discussionmentioning
confidence: 99%